Pengaruh Kompetensi Digital Dan Modal Sosial Terhadap Kinerja Guru SMA Negeri Di Kota Batam - Manalu, Nelly Chandrawati (Universitas Pendidikan Indonesia, 2024)
This research aims to analyze the influence of digital competence and social capital on the performance of high school teachers in Batam City. This research aims to find out how these two variables influence teacher performance. The method used is a qualitative method with a case study approach. The population of this research is all civil servant teachers who teach at 22 state high schools in Batam City, totaling 419 people. The total population in this study was 419 people, and the entire population was used as a sample. The results of this research indicate that the digital competency variable is an important factor that can be used in efforts to increase teacher job satisfaction. The research results show that digital competence can significantly increase the job satisfaction of public high school teachers in Batam City. The research results found that the social capital variable is an important factor that can be considered by leaders in order to increase teacher job satisfaction. The results of the research show that social capital directly has a significant effect on the job satisfaction of public high school teachers in Batam, Riau Islands Province.